Oral neglect as a marker of broader neglect: a cross-sectional investigation of orodental consultation letter of leukemic admitted patients in Iran - Fatemeh Owlia; Amin Ansarinia; Hassanali Vahedian Ardakani (BMC Oral Health, 2021)
Abstract Background Leukemia is the main malignant hematologic disease of children with different oral manifestations and clinical features. Attention to the oral manifestations is essential for better management. This study assessed the oral and dental consultations conducted in the admitted leukemic patients of an Iranian teaching hospital. Methods In this descriptive cross-sectional study, medical records of patients admitted in Yazd Shahid Sadoughi Hospital were evaluated. Records of 300 patients with leukemia were randomly selected. Data including demographic information on age, sex, type of oral problems, prescribed instructions and leukemia type were extracted from archived records and registered on the checklist. Finally, Data were analyzed by SPSS17 using Chi-square test. Results The results showed the average age ± SD of patients were 24.36 ± 23.91 with a range of 4 days to 86 years. Among 300 files, 167 belonged to males (55.7%) and 133 pertained to females (44.3%). The most prevalent type of underlying disease was ALL (Acute lymphocytic leukemia) with the frequency of 180 persons (60%). Only 12 (4%) of patients were referred to a specialist due to oral problems. Of all cases of consultation requests, 75% received consultation because of dental problems and 25% for mucosal problems. There was a statistically significant difference between age and consultation request (P = 0.002). Conclusions According to the results of this study, orodental consultation request rate for admitted leukemic patients was low. Pediatric hematologist and oncologists to some extent had more interest to consult due to oral and dental problems rather than others.